SP0141 Immune tolerance tangled in the nets: Neutrophils as a source of auto antigens. (23rd January 2014) - Scheel-Toellner, D.
Abstract : Upon activation, in an active process known as netosis, neutrophils can release their chromatin into the extracellular space. The resulting meshwork of DNA is called Neutrophil Extracellular Traps or NETS (1). These NETS are thought to retain bacteria at a site rich in neutrophil derived proteases and thus contribute to the anti-bacterial action of neutrophils. This process, therefore, is regarded as beneficial in the context of bacterial infection. However, recent studies in SLE patients suggest that in other situations, when neutrophils are activated in the context of autoimmunity, NETS can add to disease pathology (2). The release of the normally tightly packed chromatin depends on the citrullination of histone proteins (3), by an enzyme known as peptidylarginine deiminase 4 (PAD4). PAD4 and related other PAD family members have caused great interest in the research of the pathogenesis of rheumatoid arthritis. Proteins citrullinated by this group of enzymes are recognized by acpa, or anti-citrullinated protein specific antibodies. These antibodies are highly specific for rheumatoid arthritis, although their contribution to disease pathology is currently unclear. Here, we have been investigating the role of NETS in the inflamed joints of patients with rheumatoid arthritis. Most sites of chronic inflammation contain few neutrophils. An exception here is the synovial fluid (SF) of patients with chronic arthritides. The majority of the infiltrating immune cells found here are activated neutrophils. We initially quantified extracellular DNA in SF from patients with RA, OA and crystal arthritis, confirming previous reports of the presence of DNA in SF (4). Further, we applied a range of imaging technologies to generate images of NETS and attached proteins such as neutrophil elastase, PAD4 as well as citrullinated proteins. NETS were enriched from in vivo and in vitro activated neutrophils and probed for the presence of citrullinated proteins and PAD4 by western blotting. In functional experiments, we are investigating the consequences of NET generation by synovial fluid neutrophils. Taken together, our data suggest that generation of NETS by locally activated neutrophils contributes to the production of autoantigens in the inflamed joints of patients with rheumatoid arthritis. References: Brinkmann V, Reichard U, Goosmann C, Fauler B, Uhlemann Y, Weiss DS, et al. Neutrophil extracellular traps kill bacteria. Science. 2004 Mar 5;303(5663):1532-5. Garcia-Romo GS, Caielli S, Vega B, Connolly J, Allantaz F, Xu Z, et al. Netting neutrophils are major inducers of type I IFN production in pediatric systemic lupus erythematosus. Science translational medicine. 2011 Mar 9;3(73):73ra20. Wang Y, Li M, Stadler S, Correll S, Li P, Wang D, et al. Histone hypercitrullination mediates chromatin decondensation and neutrophil extracellular trap formation. J Cell Biol. 2009 Jan 26;184(2):205-13. Leon SA, Revach M, Ehrlich GE, Adler R, Petersen V, Shapiro B. DNA in synovial fluid and the circulation of patients with arthritis. Arthritis Rheum. 1981 Sep;24(9):1142-50. Disclosure of Interest: None Declared